2020
DOI: 10.3892/ijo.2020.5065
|View full text |Cite
|
Sign up to set email alerts
|

Effects of curcumin complexes on MDA‑MB‑231 breast cancer cell proliferation

Abstract: Curcumin displays anticancer properties; however, some issues with the drug delivery mode limit its therapeutic use. Although reformulation and derivatization of curcumin have improved its bioavailability, curcumin derivatives may not retain the same anticancer properties as the parent compound. The present study investigated the anticancer properties of two curcumin complexes, the iron-curcumin [Fe(Cur) 3 ] and boron-curcumin [B(Cur) 2 ] complexes, in the MDA-MB-231 breast cancer cell line. The cellular local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 106 publications
0
23
0
Order By: Relevance
“…These effects were accompanied by the regulation of Bax, Bcl-2, p16, and p21 expression, which eventually led to apoptosis induction and cell cycle arrest [ 143 ]. In contrast, it has been reported that curcumin treatment decreases the expression level of p53 and phosphorylated p53 (S392, S15, S392) in MDA-MB-231, SKBR3 and EMT6 cells, representing the induction of p53- independent apoptosis in treated cells [ 108 , 144 , 145 , 146 , 147 ]. Moreover, it has been documented that Notch1 overexpression is correlated with a highly expressed mutant p53 (R280K) in MDA-MB-231 cells, in which mutant p53 acts as its transcriptional activator.…”
Section: Curcumin: Impacts On Multiple Cellular Signaling Pathways In Hormone-independent Breast Cancermentioning
confidence: 99%
“…These effects were accompanied by the regulation of Bax, Bcl-2, p16, and p21 expression, which eventually led to apoptosis induction and cell cycle arrest [ 143 ]. In contrast, it has been reported that curcumin treatment decreases the expression level of p53 and phosphorylated p53 (S392, S15, S392) in MDA-MB-231, SKBR3 and EMT6 cells, representing the induction of p53- independent apoptosis in treated cells [ 108 , 144 , 145 , 146 , 147 ]. Moreover, it has been documented that Notch1 overexpression is correlated with a highly expressed mutant p53 (R280K) in MDA-MB-231 cells, in which mutant p53 acts as its transcriptional activator.…”
Section: Curcumin: Impacts On Multiple Cellular Signaling Pathways In Hormone-independent Breast Cancermentioning
confidence: 99%
“…Treatments against viral infections that enhance HO-1 include various anesthetics (isoflurane or sevoflurane), hemin, estrogen, statins, curcumin, resveratrol, and melatonin [ 32 ]. Therefore, HO-1 expression can be strongly induced by heme analogues, such as hemin and curcumin derivatives, such as boron–curcumin complexes [ 33 , 34 ].…”
Section: Dear Editormentioning
confidence: 99%
“…In a mouse model, this complex was shown to enhance accumulation of curcumin in the pancreas, which further potentiated gemcitabine-induced tumor growth and metastasis reduction [74]. Moreover, an iron-curcumin complex was shown to induce apoptosis and inhibit invasion of breast cancer cells [75]. As metal generates electromagnetic fields, a curcumin loaded nanoparticle with Fe 3 O 4 was prepared and tested against leukemia HL-60 cells.…”
Section: Cancermentioning
confidence: 99%